2011
DOI: 10.1179/1362171811y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

Potential of grain boundary engineering to suppress welding degradations of austenitic stainless steels

Abstract: Grain boundary phenomena strongly depend on grain boundary structure and characteristics, i.e. coincidence site lattice (CSL) boundaries, as contrasted with random boundaries, are highly resistant to intergranular degradation. Grain boundary engineering (GBE) primarily intends to prevent the initiation and propagation of intergranular degradation along random boundaries by frequent introduction of CSL boundaries into the grain boundary networks in materials. A high frequency of CSL boundaries by GBE processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Recent literature suggests different types of criteria 7 and definitions to identify the 'special' boundary. 22 In this study, the grain boundaries with low S value (S<29) were classified as CSL boundaries and Brandon's criterion 23 was adopted to define the critical deviation from the exact CSL orientation relationship, because CSL boundaries defined by these criteria could explain experimental results in our previous GBE studies, to significant extent, such as weld decay resistance, 13 percolation probabilities 29 and effects of strain sensitisation. 20 The frequency of CSL boundaries was quoted as a percentage by length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature suggests different types of criteria 7 and definitions to identify the 'special' boundary. 22 In this study, the grain boundaries with low S value (S<29) were classified as CSL boundaries and Brandon's criterion 23 was adopted to define the critical deviation from the exact CSL orientation relationship, because CSL boundaries defined by these criteria could explain experimental results in our previous GBE studies, to significant extent, such as weld decay resistance, 13 percolation probabilities 29 and effects of strain sensitisation. 20 The frequency of CSL boundaries was quoted as a percentage by length.…”
Section: Methodsmentioning
confidence: 99%
“…11 Grain boundary engineered (GBEed) materials were reported to have higher resistance to weld decay than conventional, non-GBEed, materials. 12,13 Other studies have shown that GBE is also effective to prevent various forms of grain boundary degradation in many polycrystalline materials, 14 such as segregation induced embrittlement in ultrafine grained nickel, 15 grain boundary sliding in nickel, 16 liquation cracking in weld HAZ of nickel based superalloys, 17 corrosion-erosion in 316 austenitic stainless steel 18 and intergranular corrosion due to sensitisation subsequent to carbon redissolution in stabilised 321 austenitic stainless steel. 19 In the practical use of GBEed materials as structural materials, they would be deformed and welded during manufacturing following the GBE process.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that microstructure is a typical microstructure with austenite phase stainless steel. After the rolling and subsequent annealing, the microstructure will change and contains a twin-boundary which is a part of the crystal that changes orientation to form a symmetrical twin to the original lattice [11,16]. The twinning crystal part is an inverted image of the parent crystal due to the shear stress that acts.…”
Section: Microstructurementioning
confidence: 99%
“…The cold rolling process and annealing treatment afterward change the grain's structures. These grain boundary changes have been known can be controlled to reduce the corrosion rate of austenitic stainless steel [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the next issue, there will be a paper by Palmer and co-workers 22 describing the use of synchrotron X-radiation to study austenite formation during continuous heating, and the discovery is made that the last austenite to form grows as nearly pure iron because the higher carbon regions of the original microstructure are consumed first. The paper by Kokawa on the control of crystal orientations to enhance the resistance of austenitic stainless to corrosive attack also relies on detailed characterisation and follows a long history of grain orientation engineering research from Japan 23 .…”
mentioning
confidence: 99%